PENGARUH INOVASI DAN EMPLOYEE CREATIVITY TERHADAP KINERJA KARYAWAN PADA INDUSTRI PERCETAKAN DI KABUPATEN TABANAN - Dewi, Nungky Kumala; Wibawa, I Made Artha (E-Jurnal Manajemen, 2022)
The purpose of this study was to analyze the effect of innovation and employee creativity on employee performance. The population of this study were 41 employees of the printing business who were registered at the 2019 Tabanan Regency Industry and Trade Of fice. The sampling method used was saturated sampling and data collected through interviews and questionnaires. The data analysis technique used are the Classical Assumption Test, Multiple Linear Regression Test, Determination Coefficient Test, F Test, T Test, and Dominant Variabel Test. The results of this study state that innovation has a positive and significant effect on employee performance, besides that employee creativity has a positive and significant effect on employee performance. The implication of this research is to provide an understanding that by maintaining innovation, employee creativity in the organization, so that it will improve employee performance. Keywords: innovation, employee creativity, employee performance